2012
DOI: 10.1130/g32868.1
|View full text |Cite
|
Sign up to set email alerts
|

What makes a volcano tick—A first explanation of deep multiple seismic sources in ascending magma

Abstract: At many volcanoes, low-frequency earthquakes have often been associated with the state of a volcanic system and have been employed for eruption prediction. Several models attempt to explain the generation of such earthquakes, but fail to describe their clustering in tight spatial swarms and their highly repetitive nature. We present a new model that not only explains the generation of a single event, but also accounts for the swarm behavior and cyclic activity. By considering magma rupture as a source mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 23 publications
1
65
0
Order By: Relevance
“…An example of a spatially extended source generating seismicity within a volcanic environment is a volcanic conduit through which magmatic fluids move. In these instances, the generation of low frequency seismicity may be related to the brittle failure of magma itself Lavallée et al 2008;Thomas and Neuberg 2012) or through a stick-slip motion at the conduit edge (Iverson et al 2006). In either case, shallow source depths (1-2 km) and short epicentral distances to seismic receivers (a few kilometers) suggest that a spatially extended source is more realistic than a single point source.…”
Section: The Source Mechanisms Of Low Frequency Earthquakesmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of a spatially extended source generating seismicity within a volcanic environment is a volcanic conduit through which magmatic fluids move. In these instances, the generation of low frequency seismicity may be related to the brittle failure of magma itself Lavallée et al 2008;Thomas and Neuberg 2012) or through a stick-slip motion at the conduit edge (Iverson et al 2006). In either case, shallow source depths (1-2 km) and short epicentral distances to seismic receivers (a few kilometers) suggest that a spatially extended source is more realistic than a single point source.…”
Section: The Source Mechanisms Of Low Frequency Earthquakesmentioning
confidence: 99%
“…The trigger mechanism of such seismic energy is further disputed, with suggestions that it may be generated by: (1) a stick-slip motion along the conduit walls as magma ascends (e.g. Iverson et al 2006); (2) the brittle failure of magma itself either through an increase in viscosity and strain rates (Lavallée et al 2008), which may be due to an increase in the ascent rate of magma through the conduit , changes in the crystal and/or bubble concentration in the magma (Goto 1999), or through a change in the geometry of the conduit (Thomas and Neuberg 2012); (3) the interaction between the magmatic and hydrothermal system at depth (e.g. Nakano and Kumagai 2005); or (4) through slow rupture and failure of unconsolidated material on volcanic slopes (Bean et al 2014).…”
Section: Classification By Frequency Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuberg et al (2006) further modelled magma ascent in confined geometry and showed that a De $ 1 is met at a depth of 830 m below the surface using parameters typical for recent eruptions at Soufriere Hills volcano and the magma thereof. Thomas and Neuberg (2012) predicted a deeper source of 1500 m using the same model approach but by invoking a conduit restriction (see Chap. 9), consistent with inversions for low-frequency sources using seismic data.…”
Section: Laboratory-scale Unrest Signalsmentioning
confidence: 99%
“…However, knowledge of the physics of the source leads to a more diverse range of tools being deployed to understand the evolution of volcanic systems into the future. In the context of low-frequency earthquakes at volcanoes, once a source mechanism is identified (Tuffen et al 2003;Neuberg et al 2006), numerical models of magma ascent in the conduit beneath volcanoes can be used to reproduce the depths of the source from first principles (Thomas and Neuberg 2012) and could eventually make forecasts of other observables at the surface that would be consistent with impending eruption.…”
Section: Introductionmentioning
confidence: 99%